PHILOSOPHICAL-LEGAL CONCEPTUAL FOUNDATIONS REGARDING THE RULE OF LAW AND ITS EVOLUTION. THE CORRELATION BETWEEN POLITICAL POWER, LAW AND THE RULE OF LAW - Iulian NEDELCU; Paul-Iulian NEDELCU (Challenges of the Knowledge Society)
The rule of law has been written about and will always be written about. Considered by some to be a seemingly nebulous reality, everyone talks about it, even if most of the time without explaining it. The phrase is invoked, in its name decisions are made, options are made and actions are argued. And so it becomes postulated, considered by many as a last bastion of defense against abuses of power. Throughout his life, man, an essentially social person, endowed with intelligence, felt the need to live in various forms of association, in which he shared his customs, moral and religious norms or, finally, his interests. Human activity, as a great Italian jurist and philosopher stat 1 it can be considered as being regulated by a complex system of rules; and, indeed, in every historical phase we find such a system.